A discourse of the role and impacts of Nigerian judiciary in enhancing national security (2017)
This paper discusses the role and impacts of the Nigerian Judiciary in enhancing National Security. The pertinent question which the paper resolves are: How do the judiciary function enhances national security? Is there any difference between the role performs by the judiciary in the period of emergency and at peace time? What impacts has judiciary made in maintaining the Nigerian internal security? The paper adopts the analytical method to examine the position of judiciary as the third arm of government. The paper recommends independence of judiciary to cope with the myriad of security challenges in Nigeria.